Etä- ja hybridityöskentelyn vaikutukset teknostressiin asiantuntijatyössä - Nissinen, Ella (2024)
The amount of remote working has increased strongly in recent years, due to the COVID-19 pandemic but also the digitalization and the continuous increase in the use of technology. As work becomes more technology-oriented, especially in the field of knowledge work, employees must handle increasingly large amounts of information in their work and constantly adopt the use of new systems and technologies. The increase in the use of technology can also affect employees negatively, causing additional stress. Stress caused by using technology is called technostress. Technostress is a growing problem in organizations, and it can cause significant harm to employees' well-being and work performance. The subject of this master's thesis is the technostress experienced among knowledge workers in remote and hybrid working. The subject of the research is employees who do information work, who mainly work with technology and have done both on-site and remote work. The purpose of the research is to identify factors that cause technostress in knowledge work and find out how remote working and the hybrid work model affect these factors. In addition, the goal is also to find ways to mitigate technostress. In the research carried out with thematic interviews, it was found that techno-invasion, techno-unreliability, techno-overload and techno-complexity cause technostress among knowledge workers. Technostress could be mitigated both by means of the organization, such as increasing technology literacy and providing technical support, and by means of the individual, such as peer support and disconnecting from technology. Remote working was found to have both positive and negative effects on work stress and the experience of technostress. In particular, employees found it more difficult to distance themselves from work when working remotely, while time management was significantly easier in remote work. In the technostress context, the hybrid working model was found to be the optimal option for utilizing the best aspects of remote work and on-site work.